Objective measurements of excess skin in post bariatric patients – inter-rater reliability. Issue 2 (3rd March 2016) - Biörserud, Christina; Fagevik Olsén, Monika; Elander, Anna; Wiklund, Malin
Abstract: Background : An ability to reliably assess excess skin after massive weight loss using well-described and transferrable methods is important. The aim of this trial was to evaluate inter-rater reliability of ptosis and circumference measurements in patients with excess skin after bariatric surgery. Materials and methods : Twenty-five postbariatric patients were included in the study, and their excess skin was measured 18 months after surgery. A protocol was designed to measure excess skin in a standardised way. To evaluate the inter-rater reliability in the measuring protocol, all patients were measured twice, by a specialist nurse and a specialist physiotherapist. Results : All circumference measurements on different body parts had an ICC > 0.9, indicating high reliability. Furthermore, all breast and abdominal ptosis measurements had high reliability. In contrast, visual evaluation of abdominal ptosis had poor reliability. Measurements of ptoses on different body parts had an ICC > 0.6. There were no systematic differences between the results of the two testers, except for measurements of the buttocks and maximal knee circumference. Conclusion : The measuring protocol presented in this study has high reliability and, therefore, represents a useful instrument to provide a consistent and objective assessment of excess skin in the postbariatric patient.